2022
DOI: 10.21203/rs.3.rs-1383158/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and risk factors for kidney disease in Chinese HIV-Infected patients: A cross-sectional study

Abstract: Background Kidney disease is an important comorbidity in HIV-infected patients, and is associated with poor outcomes of these patients. However, data on kidney function in Chinese HIV-Infected patients are scarce. In this study we determined the prevalence of kidney disease in PLWH involving ART-naïve patients and ART-experienced patients in China and explored its associated risk factors. Methods In the cross-sectional study, we recruited hospitalized adult HIV-infected patients. Demographic characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The prevalence of renal insufficiency in this study is comparable to other studies among ALHIV within Tanzania, which reported a prevalence of renal insufficiency (eGFR < 60 mL/min/1.73 m 2 ) of 7–10% among ALHIV in Tanzania [ 10 , 11 , 12 , 13 ]. In general, studies from SSA [ 8 , 9 , 10 , 11 , 12 ] have reported much higher rates of renal insufficiency (7–12%) among ALHIV, using similar definitions (eGFR < 60 mL/min/1.73 m 2 ), compared to studies from central-eastern Europe [ 41 ] and the Asian-pacific region [ 42 , 43 , 44 ] (4–5%), although the settings and populations within the studies were highly variable. Systematic reviews in the US have reported a prevalence of renal insufficiency of up to 15.5% among ALHIV [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of renal insufficiency in this study is comparable to other studies among ALHIV within Tanzania, which reported a prevalence of renal insufficiency (eGFR < 60 mL/min/1.73 m 2 ) of 7–10% among ALHIV in Tanzania [ 10 , 11 , 12 , 13 ]. In general, studies from SSA [ 8 , 9 , 10 , 11 , 12 ] have reported much higher rates of renal insufficiency (7–12%) among ALHIV, using similar definitions (eGFR < 60 mL/min/1.73 m 2 ), compared to studies from central-eastern Europe [ 41 ] and the Asian-pacific region [ 42 , 43 , 44 ] (4–5%), although the settings and populations within the studies were highly variable. Systematic reviews in the US have reported a prevalence of renal insufficiency of up to 15.5% among ALHIV [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The eGFR values were also categorized according to the KDIGO 2012 Clinical Practice Guideline [30]. The categories (in mL/min/1.73 m 2 ) include normal/high (≥90), mildly decreased (60-89), mild-moderately decreased (45-59), moderately-severely decreased (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), severely decreased (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and kidney failure (<15). Participants were considered smokers and alcohol users if they were currently smoking or drinking, or they quit in ≤12 months [34].…”
Section: Variablesmentioning
confidence: 99%